How global are German corporations? An empirical investigation. (10th July 2020) - Geiger, Jessica; O'Hagan-Luff, Martha
The internationalisation of firms has been subject of much debate in the field of international business, with many studies examining firm-level internationalisation using a number of different measures, but few investigating changes in these measures over time. In order to contribute to closing this gap, we conduct a longitudinal study of the patterns of internationalisation of 164 German firms from the Thomson Reuters Germany equity index between 1998 and 2015, contributing to the debate surrounding regionalisation or globalisation at the firm level. To capture different aspects of multinationality, we measure both the extent and scope of internationalisation. We further categorise these measures of internationalisation over time within categories of age, size, and industry. A strong trend towards globalisation is revealed, with most firms reporting foreign sales outside of Europe and very few operating in this region only.